Expression OF p53, p21WAF1/CIP1 , p16INK4A and Ki-67 proteins in serous ovarian tumors - Buchynska, L.G.; Nesina, I.P.; Yurchenko, N.P.; Bilyk, O.O.; Grinkevych, V.N.; Svintitsky, V.S. (Experimental Oncology, 2007)
Aim: The analysis of p53, p21WAF1/CIP1, p16INK4a and Ki-67 expression in serous ovarian carcinomas of different grade. Materials and Methods: In total, 43 ovarian adenocarcinomas and 8 non-altered ovarian epithelial tissues were immunohistochemically investigated for expression of Кі-67, р53, р21WAF1/CIP1 and р16INK4a. Results: It has been shown that expression of Кі-67, р53, р21WAF1/CIP1 and р16INK4a in non-altered ovarian epithelial tissue is absent. Serous ovarian carcinomas are characterized by high proliferative activity (PI Кі-67 = 30.0 ± 0.3%), р53 and р16INK4a overexpression (LI is 40.3 ± 0.3% and 31.1 ± 0.6% respectively) and low expression of р21WAF1/CIP1 (LI = 6.8 ± 0.3%). The association between expression of these markers and ovarian tumor grade was defined: the maximal level of Кі-67, р53 and p16/INK4a and minimal of p21WAF1/CIP1 expression were observed in G3 tumors. So, low p21WAF1/CIP1 expression (LI < 7.0%) combined with р16INK4a overexpression is considered to be the factor for a poor prognosis in serous ovarian cancer. Conclusions: The present study has indicated that biomolecular markers of cell proliferation along with traditional clinical and morphologic characteristics can be used for differential diagnostics of ovarian tumors. Цель: анализ экспрессии белков р53, р21WAF1/CIP1, р16INK4a и Кі-67 в серозных опухолях яичника разной степени дифференциации. Материалы и методы: иммуногистохимическое определение уровня экспрессии белков Кі-67, р53, р21WAF1/CIP1 и р16INK4 в образцах операционного материала 43 больных раком яичника и 8 пациенток с фибромиомой матки, эпителиальная ткань яичника которых не изменена. Результаты: установлено, что в неизмененном поверхностном эпителии яичников экспрессия белков Кі-67, р53, р21WAF1/CIP1 и р16INK4a не выявлялась. Для серозных аденокарцином характерна высокая пролиферативная активность (индекс пролиферации (ИП) Кі-67 = 30,0 ± 0,3%), гиперэкспрессия р53 (индекс метки (ИМ) = 40,3 ± 0,3%) и р16INK4 (ИМ = 31,1 ± 0,6%), а также низкий уровень экспрессии р21WAF1/CIP1 (ИМ = 6,8 ± 0,3%). Установлена зависимость уровня экспрессии изученных маркеров от степени дифференцировки серозных опухолей яичника: максимальный уровень экспрессии Кі-67, р53 и p16/INK4a и минимальный p21WAF1/CIP1 отмечали в низкодифференцированных аденокарциномах яичника. Таким образом, низкий уровень экспрессии белка p21WAF1/CIP1 (ИМ < 7,0%) с одновременной гиперэкспрессией р16INK4a можно считать фактором неблагоприятного течения серозного рака яичника. Выводы: результатыпроведенного исследования показали, что молекулярно-биологические маркеры пролиферации клеток наряду с традиционными клиническими и морфологическими характеристиками могут быть использованы для дифференциальной диагностики опухолевого процесса в яичнике.